2017
DOI: 10.1002/ccr3.903
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneo‐cutaneous fistula from spilled gall bladder calculus following laparoscopic cholecystectomy

Abstract: Key Clinical MessageInadvertent spillage of gall stones is a rare yet important cause of delayed postcholecystectomy complications. Varied presentations and difficulty in diagnosis are the hallmarks, making it crucial to have a high index of suspicion to detect and intervene appropriately. Peritoneo‐cutaneous fistulae from the retained stone can be completely excised in toto.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Kumar et al has reported one such case in 2017 where the patient has spillage and presented 8 months following index surgery. 4 Our case had similar presentation but in our case there was no spillage, as gallbladder was intact and cholecystectomy was aborted in view of difficult cholecystectomy in a district hospital initially. Incidence of abdominal wall abscess due to gallbladder rupture, bilio-cutaneous fistula with intact gall bladder due to inflammation and adhesion of fundus with the anterior abdominal wall, has already been documented in literature but no case of peritoneo-cutaneous fistula formation with intact gallbladder has been documented so far.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Kumar et al has reported one such case in 2017 where the patient has spillage and presented 8 months following index surgery. 4 Our case had similar presentation but in our case there was no spillage, as gallbladder was intact and cholecystectomy was aborted in view of difficult cholecystectomy in a district hospital initially. Incidence of abdominal wall abscess due to gallbladder rupture, bilio-cutaneous fistula with intact gall bladder due to inflammation and adhesion of fundus with the anterior abdominal wall, has already been documented in literature but no case of peritoneo-cutaneous fistula formation with intact gallbladder has been documented so far.…”
Section: Discussionsupporting
confidence: 60%
“…Fistulization has also been documented and usually occurs as colo-cutaneous or biliary-cutaneous fistula. 1,3,4 Though rare, peritoneo-cutaneous fistula has also been documented following spilled stones. Kumar et al has reported one such case in 2017 where the patient has spillage and presented 8 months following index surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The development of delayed peritoneo-cutaneous fistula has not been previously reported post-cesarean section but has been seen as a complication of difficult cholecystectomy, nephrectomy, peritoneal dialysis and secondary to perforated Dalkon shield. [3][4][5][6] Post cesarean section complications, both early and late are known since times. Even in a study dating back to 1983, the overall complication rate was 14.5% and the most common complication was infection (13.3%), in particular, endometritis (6.6%), urinary tract infection (3.1%), and wound infection (1.6%).…”
Section: Discussionmentioning
confidence: 99%
“…To date, very few cases of PCF have been reported. These include the following: a PCF secondary to a perforated Dalkon shield [ 2 ], a delayed PCF post-bilateral nephrectomy [ 3 ], a delayed PCF from non-retrieved gallstones during laparoscopic cholecystectomy [ 4 ], a PCF from spilled gall bladder calculus following laparoscopic cholecystectomy [ 5 ], a PCF secondary to skin excoriation from a large chronic incisional hernia [ 6 ], and a PCF secondary to gallstone dropped at laparoscopic cholecystectomy 20 years earlier [ 7 ]. …”
Section: Discussionmentioning
confidence: 99%